Mapping "A Situation of Open Education": Using Collaborative Relational Mapping to Explore Motivations and Constraint Among Open Educators. Issue 1 (13th December 2021) - Elias, Tanya
This short paper, analyzes "a situation of open education" using a relational map constructed in collaboration with a group of open educators as part of a larger study of the implications of scale within the field of open education. Applying situational analysis research methodology with its feminist and post-structural underpinnings, the purpose of this study is not to seek a "right" or "wrong" approach to scale but instead to invite a small group of open educators to deconstruct the concept of scale. This research approach is qualitative, critical and tentative and is written in the first person in alignment with the belief that research is neither objective nor neutral. The relational map presented offers insight into the desires of open educators to increase access, enact social justice, extend beyond the course and reach wider audiences in ways that consistently reject mass standardization. It also highlights the ways in which their efforts are constrained by overwork, a constraint that compels some open educators to adopt large-scale technologies and approaches. Building the foundation for the next stages in the larger research project, it highlights open educators' complicated relationships with scale. This paper concludes that there is a need to better differentiate the mechanisms of scale through which transformation with open education might be achieved.